Evaluation of asphalt rutting based on mixture aggregate gradation. Issue 5 (4th May 2021) - Lira, Bernardita; Ekblad, Jonas; Lundström, Robert
Abstract : Aggregate gradation is fundamental concerning asphalt pavement response to loading, especially regarding resistance to permanent deformation. This study assess, in an empirical way, the capability of a gradation-based framework to evaluate the susceptibility to permanent deformation of asphalt mixtures with varying aggregate gradation. The laboratory study was planned to isolate the effect of aggregate gradation by keeping the source of both the aggregates and the binder constant. The work consisted of testing six different asphalt mixtures with varying aggregate gradations using two different methods: wheel tracking and cyclic compression test. Results show that the testing method influences the asphalt mixtures response to loading. The combined normalised result shows a non-significant relationship between the gradation-based framework parameters and resistance to permanent deformation. Additionally, it was observed that the total amount of coarse material have an influence on mixture resistance to permanent deformation.